Analysis of 8-hydroxy-2′-deoxyguanosine in human urine using hydrophilic interaction chromatography with tandem mass spectrometry - Hosozumi, Chiemi; Toriba, Akira; Chuesaard, Thanyarat; Kameda, Takayuki; Tang, Ning; Hayakawa, Kazuichi (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2012)
► Improved sensitivity of mass spectrometric detection by HILIC column. ► A sensitive and rapid analytical method for urinary 8-hydroxy-2′-deoxyguanosine. ► Strong chromatographic retention of polar compounds under highly organic mobile phase. Urinary 8-hydroxy-2′-deoxyguanosine (8-OHdG) is a widely used noninvasive biomarker of oxidative stress. A selective, sensitive and rapid method for determining 8-OHdG in human urine was developed using hydrophilic interaction chromatography–tandem mass spectrometry (HILIC–MS/MS) with electrospray ionization. 8-OHdG and isotopically labeled 8-OHdG (internal standard) were separated on a HILIC column with a mobile phase of 10mM ammonium acetate: acetonitrile (1:9, v/v) within 10min and detected by using a positive electrospray ionization interface under the selected reaction monitoring mode. The detection limits of 8-OHdG (corresponding to a signal-to-noise ratio of 3) for the HILIC-MS/MS system and the conventional method using a reversed-phase column with MS/MS were 1.0 and 26.0fmol/injection, respectively. The proposed method makes it possible to monitor the basal level of urinary 8-OHdG from non-exposed healthy subjects and can be used for large-scale human studies.